Haemoglobin Polymorphism in Red Sokoto Goats of Nigeria (2013)
This study describes the genetic structure from the Hb locus in goats of the Red Sokoto type. The haemotypification of the individuals at the Hb locus was achieved by Cellulose acetate electrophoresis. The haemoglobin polymorphism in the Red Sokoto goat was identified in the electrophoretic field of three migration zones: the fast haemoglobin named HbA type, the intermediate migration labelled HbAHbB type and the slow haemoglobin designated HbB type. These phenotypes were determined by the two co-dominant alleles, HbA and HbB' The two alleles control three haemoglobin genotypes: two homozygotes, HbAHbA and HbBHbB, and one heterozygote, HbAHbB. The allele HbA had a higher frequency (60.4%) than the allele HbB (39.6%). The HbAHbB heterozygotes had a higher incidence in the population (64.15%) in comparison with the other two homozygous genotypes; the HbAHbA had a middling frequency (28.30%) and HbBHbB had the least occurrence (7.55%). The observed haemoglobin homozygotness (35.8%) was less than the haemoglobin heterozygotness (64.2%) in the current study. This indicates that environmental conditions, selection system or breeding methods has disturbed the Hardy-Weinberg genetic equilibrium at the Hb locus level in the population of Red Sokoto goats